2015
DOI: 10.1002/2015gl064865
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Sun speed of CMEs and the magnetic nonpotentiality of their source active regions

Abstract: We show that the speed of the fastest coronal mass ejections (CMEs) that an active region (AR) can produce can be predicted from a vector magnetogram of the AR. This is shown by logarithmic plots of CME speed (from the SOHO Large Angle and Spectrometric Coronagraph CME catalog) versus each of ten AR‐integrated magnetic parameters (AR magnetic flux, three different AR magnetic‐twist parameters, and six AR free‐magnetic‐energy proxies) measured from the vertical and horizontal field components of vector magnetog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 70 publications
2
8
0
Order By: Relevance
“…The association between the 24-hour average values of the parameters and the linear speed of the CMEs is illustrated in Figure 8. These plots show basically what has been asserted in previous studies, namely that the maximum anticipated speed of a CME increases as the property value increases (Tiwari et al, 2015). For some properties (i.e.…”
Section: Mpil-related Parameters and Cme Kinematic Characteristicssupporting
confidence: 88%
See 1 more Smart Citation
“…The association between the 24-hour average values of the parameters and the linear speed of the CMEs is illustrated in Figure 8. These plots show basically what has been asserted in previous studies, namely that the maximum anticipated speed of a CME increases as the property value increases (Tiwari et al, 2015). For some properties (i.e.…”
Section: Mpil-related Parameters and Cme Kinematic Characteristicssupporting
confidence: 88%
“…This was showcased by Murray et al (2018) who combined CME detections and characteristics from the EU Framework Package 7 HELCATS project (www.helcats-fp7.eu) with active-region magnetic properties from the EU Horizon 2020 FLARECAST (flarecast.eu/) project. Although correlations tend to weaken in larger samples, general trends persist and, moreover, an upper limit on CME speeds may be imposed by magnetic non-potentiality parameters (Tiwari et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…The study found that the highest-performing features, which characterise the non-potentiality of the magnetic field, are the mean horizontal gradient of the magnetic field and the twist parameter. A study by Tiwari et al (2015) found that active regions with a larger non-potentiality and total magnetic flux can produce both fast and slow CMEs, whereas smaller active regions with a more potential configuration can only produce slower CMEs. One key factor that plays a key role in CME productivity is the configuration of the overlying field (Török & Kliem 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Although in this Letter we present the method by applying it to the simplest-to-measure magnetic parameter of an AR, the total magnetic flux, the method is suitable for correcting the magnitude (absolute value) of any whole-AR magnetic parameter, e.g., the various size, twist and freeenergy proxies studied in Tiwari et al (2015) and Bobra and Couvidat (2015). Correcting freeenergy proxies out to 60 o from disk center is needed for improving forecasting of AR's CME/flare productivity.…”
Section: Discussionmentioning
confidence: 99%